Electro-mechanical (dys-)function in long QT syndrome type 1. (1st January 2019) - Ziupa, David; Menza, Marius; Koppermann, Susanne; Moss, Robin; Beck, Julia; Franke, Gerlind; Perez Feliz, Stefanie; Brunner, Michael; Mayer, Sonja; Bugger, Heiko; Koren, Gideon; Zehender, Manfred; et al.
Abstract: Background: Prolonged repolarization is the hallmark of long QT syndrome (LQTS), which is associated with subclinical mechanical dysfunction. We aimed at elucidating mechanical cardiac function in LQTS type 1 (loss of I Ks ) and its modification upon further prolongation of the action potential (AP) by I Kr -blockade (E-4031). Methods: Transgenic LQT1 and wild type (WT) rabbits ( n = 12/10) were subjected to tissue phase mapping MRI, ECG, and epicardial AP recording. Protein and mRNA levels of ion channels and Ca 2+ handling proteins ( n = 4/4) were determined. In silico single cell AP and tension modeling was performed. Results: At baseline, QT intervals were longer in LQT1 compared to WT rabbits, but baseline systolic and diastolic myocardial peak velocities were similar in LQT1 and WT. E-4031 prolonged QT more pronouncedly in LQT1. Additionally, E-4031 increased systolic and decreased diastolic peak velocities more markedly in LQT1 – unmasking systolic and diastolic LQT1-specific mechanical alterations. E-4031-induced alterations of diastolic peak velocities correlated with the extent of QT prolongation. Conclusion: While baseline mechanical function is normal in LQT1 despite a distinct QT prolongation, further prolongation of repolarization by I Kr -blocker E-4031 unmasks mechanical differences between LQT1 and WT with enhanced systolic and impaired diastolic function only in LQT1. These data indicate an importance of the extent of QT prolongation and the contribution of different impaired ion currents for conveying mechanical dysfunction. Highlights: Despite QT prolongation, baseline systolic/diastolic function is unaltered in LQT1. Further QT prolongation by E-4031 improves systolic function in LQT1. Further QT prolongation by E-4031 decreases diastolic function in LQT1. The extent of QT prolongation correlates with the extent of mechanical (dys-)function.